2020
DOI: 10.1111/mec.15597
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of stream macroinvertebrate communities with eDNA is not congruent with tissue‐based metabarcoding

Abstract: Freshwater habitats are particularly sensitive to changes caused by anthropogenic stress, including habitat degradation, pollution and alteration of water inputs and flow (Dudgeon et al., 2006).Bioindicators are species or taxonomic groups that respond predictably to environmental changes (Cairns & Pratt, 1993) and are often used to evaluate the degree of disturbance or habitat impairment (Norris & Hawkins, 2000). Aquatic macroinvertebrates are commonly used bioindicators in both lentic and lotic systems (Bona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 67 publications
4
62
0
2
Order By: Relevance
“…Analysis with universal primer pair BF2/BR2 recovered mostly nontarget taxa, especially diatoms, similar to reported observations from other studies using universal COI primers (Beentjes et al., 2019; Deiner et al., 2016; Gleason et al., 2020; Hajibabaei, Porter, Robinson, et al, 2019; Macher et al., 2018), leaving only a small number of reads and OTUs of target taxa recovered from the extracted eDNA. The amplification of nontarget DNA from extracted eDNA samples was consistently observed across all 20 samples.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Analysis with universal primer pair BF2/BR2 recovered mostly nontarget taxa, especially diatoms, similar to reported observations from other studies using universal COI primers (Beentjes et al., 2019; Deiner et al., 2016; Gleason et al., 2020; Hajibabaei, Porter, Robinson, et al, 2019; Macher et al., 2018), leaving only a small number of reads and OTUs of target taxa recovered from the extracted eDNA. The amplification of nontarget DNA from extracted eDNA samples was consistently observed across all 20 samples.…”
Section: Discussionsupporting
confidence: 87%
“…A similar comparison was performed by Gleason et al. (2020) in Canada, also reporting only 12% of the eDNA reads being assigned to benthic invertebrate taxa as opposed to 99% of the reads in bulk samples. Similarly, Beentjes et al.…”
Section: Introductionmentioning
confidence: 99%
“…Once samples were filtered (approximately 4-20 min per sample), we placed the filter in a sterile petri dish and stored in the samples at −80 • C until DNA extraction. We used a CTAB extraction protocol for ethanol eDNA (see [25,29]), quantified and normalized DNA concentration of all samples to 5 ng/µL.…”
Section: Edna Filtration and Extractionmentioning
confidence: 99%
“…This can account for the absence of some species and a subsequent reduction in biodiversity observed in previous studies comparing sampling methods [24]. While some research suggests that eDNA metabarcoding water samples is an appropriate substitute for kick-net sampling (e.g., [15,21,22]), other studies have preferred bulk sample metabarcoding [24,25]. Gleason et al [25] compared invertebrate community composition between tissue samples and eDNA samples and found that eDNA mostly amplified algae, with minimal overlap in invertebrate community composition between paired bulk tissue and eDNA samples collected from the same location.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation